Estratégias de cooperação no aglomerado de malhas retilíneas de Nova Petrópolis - Neumann, Leonardo (Universidade do Vale do Rio do Sinos, 2007)
The increasing competitive challenges have been requiring new answers and strategies from the companies as a means of assuring their survival, mainly if they are small size firms where the restrictions and difficulties are even higher. The textile sector has as natural characteristics a strong fragmentation due to historical factors, low entrance barriers, absence of scale economies or experience curves, seasonal sales and low bargain power. Inside the textile sector, we find the knitting industry that is the study object through the analysis of the knitting cluster from Nova Petrópolis. One of the main goals of this research is to evaluate the existence of cooperation relationships among the one hundred or more firms located in this city. These interrelations may strengthen competitive gains for the participants and in reality are complementary and collective strategies. The cooperation can bring various benefits where we can highlight the collective learning, market enlargement, costs and risks reduction,
Keywords: pequeno porte; aglomerados; empresas; indústria fragmentada; malharias; micro porte; relações interorganizacionais; setor têxtil; cooperação; clusters; fragmented industry; interorganizational relations; knitting firms; small companies; textile sector; cooperation; Ciências Sociais Aplicadas